The value of flexibility in conservation financing. Issue 3 (20th March 2017) - Lennox, Gareth D.; Fargione, Joseph; Spector, Sacha; Williams, Gwyn; Armsworth, Paul R.
Abstract: Land‐acquisition strategies employed by conservation organizations vary in their flexibility. Conservation‐planning theory largely fails to reflect this by presenting models that are either extremely inflexible—parcel acquisitions are irreversible and budgets are fixed—or extremely flexible—previously acquired parcels can readily be sold. This latter approach, the selling of protected areas, is infeasible or problematic in many situations. We considered the value to conservation organizations of increasing the flexibility of their land‐acquisition strategies through their approach to financing deals. Specifically, we modeled 2 acquisition‐financing methods commonly used by conservation organizations: borrowing and budget carry‐over. Using simulated data, we compared results from these models with those from an inflexible fixed‐budget model and an extremely flexible selling model in which previous acquisitions could be sold to fund new acquisitions. We then examined 3 case studies of how conservation organizations use borrowing and budget carry‐over in practice. Model comparisons showed that borrowing and budget carry‐over always returned considerably higher rewards than the fixed‐budget model. How they performed relative to the selling model depended on the relative conservation value of past acquisitions. Both the models and case studies showed that incorporating flexibility through borrowing or budget carry‐over gives conservation organizations the ability to purchase parcels of higher conservation value than when budgets are fixed without the problems associated with the selling of protected areas.